ANALISIS IMPLEMENTASI SURAT EDARAN KEMENTERIAN PERHUBUNGAN NOMOR 13 TAHUN 2020 DI BANDAR UDARA INTERNASIONAL YOGYAKARTA - Adhinda Zhalzabila Qatrunnada; Zenita Kurniasari (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2023)
At the end of 2019 the world was shocked by the presence of a new virus, namely the corona virus. The more people who gather in a confined space, the greater the risk of transmission of the corona virus. The airport is a gathering place for many people or individuals from various countries and regions that have the potential to spread viruses or infectious diseases, by implementing health protocols at airports it is hoped that it can help control the spread of disease and can give passengers confidence to travel safely by using transportation air. This study uses qualitative methods with data collection techniques through interviews, observation, and documentation. Then proceed with data analysis techniques, namely data reduction, data presentation, and drawing conclusions. The results obtained in this study are that Yogyakarta International Airport has implemented the health protocol according to the Ministry of Transportation Circular Letter Number 13 of 2020 properly. However, there have been several obstacles in implementing health protocols in recent years due to the transition from SE 13 of 2020 regulations to the Ministry of Home Affairs regulations 53 of 2022, where Yogyakarta International Airport is adjusting to new regulations and ensuring that old regulations are not neglected.